Synchronization of Transmembrane Na+ And K+ Traffic in the Epidermis is Evidence of the Criticality of Na+/K+-ATPase Function - Petukhov, V.I.; Dmitriev, E.V. (Journal of Antioxidant Activity, 2026)
Hair spectrometry results for sodium and potassium content in healthy individuals (n = 9991) were analyzed using mathematical statistics. It was found that the vast majority (81.6%) of the overall group had a (Na)/(K) ratio > 1, with a median (Me) of 2.35. However, 18.4% had a ratio < 1 (Me = 0.68). The median (Na)/(K) for the overall group was 1.98. Of particular interest was the analysis of the distribution of (Na) and (K) depending on the (Na)/(K) ratio. The results of this analysis are presented in the article.
Keywords: sodium oxide; metal-ligand homeostasis; self-organized criticality; epidermis; hair